2001
DOI: 10.1099/00221287-147-12-3263
|View full text |Cite
|
Sign up to set email alerts
|

A σ54-dependent PTS permease of the mannose family is responsible for sensitivity of Listeria monocytogenes to mesentericin Y105

Abstract: Sensitivity of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
198
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(207 citation statements)
references
References 24 publications
6
198
1
2
Order By: Relevance
“…monocytogenes (Dalet et al, 2001). However, we subsequently observed that MptA was not expressed in the mptD deletion mutant, suggesting that the entire operon is switched off in this mutant (Gravesen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…monocytogenes (Dalet et al, 2001). However, we subsequently observed that MptA was not expressed in the mptD deletion mutant, suggesting that the entire operon is switched off in this mutant (Gravesen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…monocytogenes showing highlevel resistance to class IIa bacteriocins (Gravesen et al, 2002). This IIAB is part of the EII Man t permease encoded by the mptACD operon (Dalet et al, 2001). Genetic inactivation of the mptACD operon resulted in resistance to mesentericin Y105 in Ls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of this gene was highly suppressed after incubation for 240 h at 4 °C, and the treatment with nisin resulted in lower dltA expression as compared with the peptide P34. Previous studies have shown that a 1000-fold increased resistance to class IIa bacteriocins in L. monocytogenes and Enterococcus faecalis resulted from the loss of mptA expression [38,42,43]. The cell wall of L. monocytogenes is composed by a thick peptidoglycan layer containing two types of anionic polymers: teichoic acids (TA), which are covalently linked to the peptidoglycan, and lipoteichoic acids (LTAs), which are poly phosphoglycerols substituted with a Dalanyl ester or a glycosyl residue and anchored in the membrane by their glycolipid moiety [44].…”
Section: Resultsmentioning
confidence: 99%
“…By inactivating this operon by directed mutagenesis in L. monocytogenes and E. faecalis, the mutant strains displayed high resistance to the class IIa bacteriocin mesentericin Y105 (Dalet et al 2001;Hechard et al 2001). Heterologous expression of mptACD operon of L. monocytogenes in an insensitive Lc.…”
Section: Class Iia Bacteriocinsmentioning
confidence: 99%